Perlindungan Hukum Ibu Pengganti (Surrogacy) di Indonesia: Menimbang Hak Reproduksi, Kepentingan Anak, dan Martabat Perempuan - Dielasy Budiarti; Yandi Saputra (Pusat Riset dan Inovasi Nasional, 2025)
The practice of surrogacy in Indonesia is growing despite the absence of clear legal regulations, creating uncertainty in the protection of surrogates, children, and those who use surrogacy services. Although several countries have regulations governing this practice, Indonesia still faces a legal vacuum that leaves many parties vulnerable to exploitation. This study aims to analyze aspects of legal protection, reproductive rights, children's interests, and women's dignity in the context of surrogacy in Indonesia, with the aim of formulating a more adaptive and equitable regulatory framework. The method used in this study is a normative juridical approach, with analysis using AMOS-based Structural Equation Modeling (SEM) of relevant legal documents and existing scientific literature. This research involves an analysis of existing regulations, cases related to surrogacy, and the opinions of legal experts and the public. The results show significant differences in legal protection between surrogates and children involved in surrogacy practices. Furthermore, there is uncertainty regarding the status of children born through surrogacy practices, which impacts their rights, particularly in terms of legal recognition and access to their human rights. This study also emphasizes that protecting women's reproductive rights and maintaining their dignity must be an integral part of surrogacy regulations. Clear and comprehensive regulations have been shown to improve protection for surrogates, children, and other related parties, as well as prevent potential exploitation. The implications of this study are the importance of establishing legislation specifically governing surrogacy practices in Indonesia, where such policies must focus on justice, child rights protection, and gender equality.